2019
DOI: 10.1146/annurev-genet-112618-043650
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Aging

Abstract: Aging is a natural process of organismal decay that underpins the development of myriad diseases and disorders. Extensive efforts have been made to understand the biology of aging and its regulation, but most studies focus solely on the host organism. Considering the pivotal role of the microbiota in host health and metabolism, we propose viewing the host and its microbiota as a single biological entity whose aging phenotype is influenced by the complex interplay between host and bacterial genetics. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 156 publications
6
112
0
Order By: Relevance
“…He showed that fecal transplantation of young microbiota to old animals rescued age-dependent decrease in abundance of microbiota and extended the lifespan of the fish. Modulation of microbial function can also impact the effect of potential pharmacological interventions in hosts, as was highlighted by Filipe Cabreiro, Imperial College London, UK, who suggested that age-dependent changes in gut microbial composition can be potentially considered one of the hallmarks of aging [15]. Using the well-known pro-longevity drug metformin and a combination of model organisms such as C. elegans and D. melanogaster together with computational approaches for modelling human microbiome data, Filipe"s team showed that diet can impact the beneficial effect of metformin.…”
Section: Agingmentioning
confidence: 99%
“…He showed that fecal transplantation of young microbiota to old animals rescued age-dependent decrease in abundance of microbiota and extended the lifespan of the fish. Modulation of microbial function can also impact the effect of potential pharmacological interventions in hosts, as was highlighted by Filipe Cabreiro, Imperial College London, UK, who suggested that age-dependent changes in gut microbial composition can be potentially considered one of the hallmarks of aging [15]. Using the well-known pro-longevity drug metformin and a combination of model organisms such as C. elegans and D. melanogaster together with computational approaches for modelling human microbiome data, Filipe"s team showed that diet can impact the beneficial effect of metformin.…”
Section: Agingmentioning
confidence: 99%
“…Like oncology prior to the emergence of the oncogene paradigm, it is characterised by a diversity of competing theories and approaches, which drift in and out of fashion. Other factors that could just as well have appeared on the list include antagonistic pleiotropy or trade-offs (Williams 1957;Partridge & Barton 1993), inflammation and inflammaging (Franceschi et al 2000;, consequences of mechanical senescence (Comfort 1964), altered endocrine function (Tatar et al 2003 (Kim & Choe 2019), immune senescence leading to increased infection (Aw et al 2007;Fulop et al 2013) and, if the list were being drawn up today, dysbiosis of the microbiome (Bana & Cabreiro 2019).…”
Section: Measuring the Hallmarks Of Aging Against The Hallmarks Of Cancermentioning
confidence: 99%
“…Diet and microbiome: Microbiome dysbiosis has recently been proposed as an additional hall mark of ageing (Bana and Cabreiro, 2019) as microbial changes have been reported in many age associated diseases (García-Peña et al, 2017). At the same time, specific diets (e.g.…”
Section: Common Featuresmentioning
confidence: 99%